Famotidine for COVID-19 - Chrisnanda, Anang Agung; Saputro, Anjar Hermadi (Pharmacy Reports, 2023)
Famotidine has emerged as a candidate for COVID-19 treatment, with various studies investigating its impact on the virus. These studies have reported encouraging results, suggesting that famotidine might contribute to fighting COVID-19 by potentially blocking histamine release, TMPRSS, and fortifying glycocalyx. Clinical trials aimed at assessing the effectiveness of famotidine in patients with COVID-19 have observed that it contributed to quicker alleviation of symptoms and reduction in inflammation, without compromising the body's immunity against SARS-CoV-2. However, in the case of patients with severe illness, famotidine's use did not significantly enhance survival rates. Although further investigation is necessary, famotidine has shown promise in alleviating symptoms and reducing inflammation in COVID-19 cases.